1998
DOI: 10.1046/j.1523-1747.1998.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Type II Cytokeratin, K6hf, Specifically Expressed in the Companion Layer of the Hair Follicle

Abstract: In an attempt to identify new members of the human type II hair keratin family by means of 3'- and 5'-RACE methods and cDNA from anagen hair follicles, we detected a sequence that encoded a hitherto unknown type II cytokeratin. The novel cytokeratin comprises 251 amino acids and exhibits the highest sequence homology with K5. Comparative one- and two-dimensional western blots of keratins from anagen hair bulbs, containing or not containing the outer and inner root sheaths (ORS/IRS), and from footsole epidermis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 36 publications
10
164
0
Order By: Relevance
“…7D). Moreover, the cytokeratin K6hf, which is specifically expressed in the companion cell layer of wild-type follicles (Winter et al 1998), was detected throughout the IRS as well as in the cortex of Cutl1 Z/Z follicles (Fig. 7E).…”
Section: Abnormal Differentiation Of the Inner Root Sheath In Cutl1 Mmentioning
confidence: 96%
See 1 more Smart Citation
“…7D). Moreover, the cytokeratin K6hf, which is specifically expressed in the companion cell layer of wild-type follicles (Winter et al 1998), was detected throughout the IRS as well as in the cortex of Cutl1 Z/Z follicles (Fig. 7E).…”
Section: Abnormal Differentiation Of the Inner Root Sheath In Cutl1 Mmentioning
confidence: 96%
“…In contrast, however, the companion cells are in intimate contact with cells of Henlé's layer through desmosomes and gap junctions and therefore may form a slippage plane to allow the growing hair fiber to move along the ORS (Rothnagel and Roop 1995). Moreover, the elongated and vertically oriented companion cells are also morphologically and biochemically distinct from the cuboidal ORS cells, which has led to the hypothesis that the companion cells constitute an independent histological compartment of the hair follicle (Rothnagel and Roop 1995;Winter et al 1998). The coexpression of Cutl1 in the IRS and companion cells now strongly argues that the companion cells constitute the fourth and outermost layer of the IRS.…”
Section: Cutl1-dependent Cell Fate Specification In Hair Follicle Devmentioning
confidence: 99%
“…Our results indicate that primary skin stem cells as well as the Tel-E6E7 cell line are able to differentiate into epidermal, hair follicle and sebaceous lineages. For in vitro hair differentiation, expression of Keratin 6 hair follicle (K6hf), which is specifically expressed in the companion layer of the hair follicle (Winter et al 1998), increased after co-culture with dermal papilla cells for 2 days ( Figure 4A). We previously showed that this induction of hair differentiation depended on active Wnt-β-catenin signaling (Roh et al 2004).…”
Section: Multi-potentialitymentioning
confidence: 99%
“…The alternative is for the layer to move with the IRS as that layer differentiates with the growing hair. Families of K6 proteins together with K16 (Rothnagel and Roop, 1995, Takahashi et al, 1995, Winter et al, 1998) are expressed in the companion layer and presumably they correspond to the keratin IFs seen in the cells.…”
Section: Outer Root Sheathmentioning
confidence: 99%